One-pot synthesis of 3D Au nanoparticle clusters with tunable size and their application. (26th November 2019) - Wang, Liwei; Liu, Guixian; Han, Junhe; Li, Ruoping; Liu, Junhui; Chen, Ke; Huang, Mingju
Abstract: In general, the preparation of Au nanoparticle clusters (NPCs) is more challenging than that of nanoparticles. The traditional multi-step method for preparing Au NPCs is time consuming and highly sensitive to the reaction conditions. Here, we report a simple and feasible method for the rapid preparation of Au NPCs (∼30 min), in which Au (III) is reduced to Au (0) by trisodium citrate, and assembled into NPCs in the presence of a trace amount of cysteine. The surface plasmon resonance peak of the Au NPCs is tunable and ranged from visible to near-IR regions by varying the content of cysteine added. The growth process of Au NPCs was monitored by dynamic light scattering, UV–vis absorption spectroscopy and transmission electron microscopy. Their elemental composition, chemical state and molecular structure of the sample surface were measured by x-ray photoelectron spectroscopy. The proposed synthesis mechanism has guiding significance for the preparation of other NPCs. Au NPCs used as surface-enhanced Raman spectroscopy substrate has a good enhancement effect because of its unique morphology.